Synthesis of novel flower-like PtCo–Bi2MoO6 photocatalysts with enhanced visible light photocatalytic performance. Issue 87 (6th September 2016) - Lu, Yan; Li, Xiaoxuan; Han, Changcun; Ge, Lei; Fang, Siman; Qiu, Ping
Abstract : A novel PtCo/Bi2 MoO6 composite photocatalyst was successfully synthesized by loading PtCo alloy nanoparticles via a simple polyol reduction method. Abstract : A novel PtCo/Bi2 MoO6 composite photocatalyst was successfully synthesized by loading PtCo alloy nanoparticles via a simple polyol reduction method. The as-prepared PtCo/Bi2 MoO6 composite exhibits an enhanced photocatalytic performance for the degradation of RhB under visible-light irradiation. Among various PtCo/Bi2 MoO6 composites with different contents of PtCo, the 1 wt% PtCo–Bi2 MoO6 sample shows the highest photocatalytic activity and its degradation constant is 5 times higher than that of pure Bi2 MoO6 . Through photocatalytic experiments, the fabricated PtCo/Bi2 MoO6 composite demonstrated that it can efficiently promote the separation efficiency. X-ray diffraction (XRD), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS) results confirm the composition of the PtCo alloy in the composite catalysts. TOC measurement also suggests that RhB is easily mineralized. SPS measurements illustrate that the high activity of PtCo–Bi2 MoO6 could be attributed to its better ability to grab photoexcited electrons compared with Pt–Bi2 MoO6 . Based on experimental results, we propose a possible photocatalytic mechanism of PtCo–Bi2 MoO6, which may provide a theoretical basis for future research.